Pengaruh Latihan Dribbling With A Curving Line Trajectory Untuk Meningkatkan Keterampilan Dribbling Pemain Sepak Bola Ps. Undikam Mataram Tahun 2019 - Ismail Marzuki; Soemardiawan Soemardiawan (JUPE : Jurnal Pendidikan Mandala, 2019)
The focus of the problem in this research When competing frequently there are mistakes in dribbling, so from this it is necessary to have this exercise, to improve the dribbling skills of PS players. UNDIKMA Mataram. The purpose of this study is to determine whether there is an effect of Dribbling With A Curving Line Trajectory Exercise on the Dribbling Skills of PS Soccer Players. Mataram UNDIKMA 2019 ". The research methods used by researchers are the observation method, the documentation method and the deed test method. The study design uses a pretest-posttest design (initial test and final test). The population used in this study are all PS players. UNDIKMA Mataram in 2019. The number of samples in the study conducted was 22 which became a sample of 11 players PS soccer players. UNDIKMA Mataram. The sampling technique in this study using the saturation sampling technique is a sampling technique if all members of the population can be sampled. Analysis of statistical data with a significance level of 5% for the speed test results obtained by the t-value so from the results of research X1 (Dribbling With A Curving Line Trajectory, with Y1 obtained tcount is much greater than ttable, this shows that the hypothesis "Ha" (accepted ) then this research is significant, drawing conclusions from the table analysis at a significant level of 5% with a number of samples (n - 1) that is 11-1 = 10 at 1,812. Then it can be concluded that, 1) The Effect of Dribbling With A Curving Line Trajectory on Dribbling Skills PS Football Players. Mataram UNDIKMA 2019, Tcount> ttable (7.362> 1,812). 2). this shows that the hypothesis "Ha" (accepted) then this research is significant.